Existence and uniqueness of solutions for a Neumann boundary-value problem - Benmansour, Safia; Bouchekif, Mohammed (My University, 2011)
In this article, we show the existence and uniqueness of positive solutions for perturbed Neumann boundary-value problems of second-order differential equations. We use a fixed point theorem for general -concave operators.
Keywords: Positive solution; existence and uniqueness; normal cone; -concave operator; Green’s function